OC-041 Eosinophilic oesophagitis – a uk dgh experience. (22nd June 2015) - Osuoha, G; Nimalanathan, S; Kumar, M
Abstract : Introduction: Eosinophilic oesophagitis (EOE) is an immune/antigen mediated chronic inflammatory disease of the oesophagus. Its incidence and prevalence appears to be increasing and in some studies incidence has been reported to be similar to inflammatory bowel disease. Despite this EOE is largely underdiagnosed. International Guidelines recommend at least 2–4 biopsies from each of the proximal and mid/distal oesophageal segments in patients suspected to have EOE. 1 We retrospectively assessed our practice in investigating patients presenting with dysphagia and food bolus obstruction (FBO) to two district general hospitals (DGH) over a year. Method: Patients with history of dysphagia and FBO over 2014 were identified through electronic endoscopy database. 751 patients underwent gastroscopies for above complaints. Patient symptoms, demographics, endoscopic and histological findings were recorded. EOE was defined as the presence of >15 eosinophils per high power field (HPF). Results: Patients with oesophageal malignancy (n = 67), Barrett's oesophagus (n = 68), reflux oesophagitis (n = 154), post-oesophageal surgery complications (n = 6) and PEG insertions (n = 14) were excluded from the final analysis. Of the 442 remaining patients, (255 female, mean age 66; range 17–94, 187 male, mean age 64; range 17–93), oesophageal biopsies were taken from 98 patients giving a biopsy rate of 22% (98/442). 33 patients were suspected of having EOE at timing of endoscopy of which 8 (24%) confirmed cases of EOE (7 male: mean age 37; range 20–50). Endoscopy showed mucosal features in 5/8 (furrowing and corrugated rings seen), 2/8 had mild stricturing or schatzki ring. The remaining patients had Grade A-B reflux oesophagitis. Average number of biopsies taken was 7. Mean number of eosinophils HPF were 27 (range 15–40). Physicians collected more biopsies with 67% (66/98) of cases and suspected EOE in 82% (27/33). Conclusion: Only 22% of patients with symptoms conducive with EOE were biopsied, with 24% (8/33) confirmed cases if suspected. Despite recent increasing awareness of EOE, 78% (344/442) of patients did not have biopsies and only a third (31/98) of patients having the recommended number of biopsies. In summary, our DGH experience has shown that EOE detection is likely to improve further if all patients with symptoms conducive with EOE (e.g. solid food dysphagia) routinely trigger an EOE biopsy protocol of ≥4 from the mid/proximal oesophagus regardless of endoscopic findings. 2 Continuous education and improving awareness amongst clinicians who perform upper GI endoscopy will improve identification of EOE patients. Disclosure of interest: None Declared. References: Dellon ES, Gonsalves N, Hirano I, et al . ACG clinical guideline: evidenced based approach to the diagnosis and management of esophageal eosinophilia and eosinophilic esophagitis. Am J Gastroenterol. 2013;108:679–692; doi:10.1038/ajg.2013.71 Kanakala V, Lamb CA, Haigh C, et al . The diagnosis of primary eosinophilic oesophagitis in adults: missed or misinterpreted?. Eur J Gastroenterol Hepatol. 2010;22(7):848–5